The Role of Gaseous Molecules in Traumatic Brain Injury: An Updated Review - Che, Xiaoru; Fang, Yuanjian; Si, Xiaoli; Wang, Jianfeng; Hu, Xiaoming; Reis, Cesar; Chen, Sheng (Frontiers in Neuroscience, 2018)
Traumatic brain injury (TBI) affects millions of people in China each year. TBI has a high mortality and often times a seriousprognosis. The causative mechanisms of TBI during development and recovery from an injury remain vague, leaving challenges for the medical community to provide treatment options that improve prognosis and provide an optimal recovery. Biological gaseous molecules including nitric oxide (NO), carbon monoxide (CO), hydrogen sulphide (H2S) and molecular hydrogen (H2) have been found to play critical roles in physiological and pathological conditions in mammals. Accumulating evidence has found that these gaseous molecules can execute neuroprotection in many central nervous system (CNS) conditions due to theirhighlypermeable properties allowing them toenter the brain.Considering the complicated mechanisms and the serious prognosis of TBI, effective and adequate therapeutic approaches are urgently needed. These four gaseous molecules can be potential attractive therapeutic intervention on TBI. In this review, we will present a comprehensive overview on the role of these four biological gases in the development of TBI and their potential therapeutic applications.